The dynamics of waves interacting with the Equatorial Undercurrent - Constantin, A; Johnson, R.S. (Geophysical and astrophysical fluid dynamics, 2015)
We propose a new, simple model - but one which has far-reaching consequences - to describe the interaction between waves that propagate across the Pacific Ocean and the Equatorial Undercurrent (EUC). This involves a detailed discussion of the full linear problem as it relates to the dynamic coupling between the surface waves and the internal waves on the thermocline. The result is a comprehensive description of the system close to the Equator, and how the structure of the EUC affects the wave properties; in particular, the analysis holds for arbitrary wavelengths and finite depths. Although the final expressions, for general wavelengths, are too cumbersome for direct interpretation, we are able to produce simple formulae for the speeds of the waves, and the attenuation factor between the two families of waves, for short, intermediate and long waves. Further, our results predict the appearance of critical layers under certain circumstances; by reverting to our original system of governing equations, we are able to derive the relevant nonlinear structure of the flow in these layers. Our results are in good agreement with the available field data.